Dynamics of Regulatory Policymaking in Sweden: The Role of Media Advocacy and Public Opinion. (28th January 2018) - Rasmussen, Anne; Romeijn, Jeroen; Toshkov, Dimiter
Abstract : While extensive literatures study the responsiveness of policy to public opinion and the influence of interest groups, few studies look at both factors simultaneously. This article offers an analysis of the influence of media advocacy and public opinion on political attention and policy change for four regulatory issues over a relatively long period of time in Sweden. The data pools together measures of public support for specific policies with new data on attention to the policy issues in the Swedish parliament, policy developments over time and detailed coding of the claims of interest advocates in two major Swedish newspapers. Analyzing this data, a complex picture without a general tendency for either public opinion or media advocacy to act as dominant forces in producing policy change is revealed, although some evidence is found that the public is successful in stimulating political attention when it supports policy proposals aimed at changing the status quo.